Implementasi Model Pembelajaran Problem Based Learning Untuk Meningkatan Hasil Belajar IPAS Peserta Didik Kelas IV-B SDN Pakis 1 Surabaya - Puji Ayu Dewi Lestari; Bekti Wirawati; Nunuk Suliyastuti (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
This research is classroom action research that aims to improve learning outcomes in Natural and Social Sciences (IPAS). The topic is changing forms of energy in class IV-B students, SDN Pakis 01 Surabaya. The number of students in the class consists of 25. The data collection method used consists of observation, tests, and documentation. The learning model applied is problem-based learning (PBL). The research results show that the learning model Problem-Based Learning (PBL) can significantly improve student learning outcomes in science subjects. The pre-cycle results showed a completion rate of 32%; in cycle 1, it increased to 56%, and then in cycle 2, it increased to 80%. Implementation of learning models (problem-based learning) has succeeded in achieving the expected targets and can effectively improve student learning outcomes, especially in class IV-B at SDN Pakis 1 Surabaya in the 2024-2025 academic year. The learning model of problem-based learning (PBL) is also known for its effectiveness in building students' critical thinking skills so that it can help make the learning process easier.